Promocja w Internecie jako element budowy przewagi konkurencyjnej w przedsiębiorstwach przemysłu spożywczego - Strzębicki, Dariusz (Internet Promotion as a Tool of Creating Competitive Advantage in the Food Industry Enterprises, 2006)
The paper discusses differences between food industry enterprises in promotional activities on their web sites. One of the main factors causing the differences is the main receiver of WWW promotional message. Web sites for consumers tend to be more multimedia and interactive comparing with web sites aiming at middlemen. Enterprises introducing new capabilities in the Internet communication before its competitors achieve advantage in Internet marketing communication.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 365-370